Page from Ledgerbook - Unknown:::Creator::::::::::::
Steinbeck's handwritten ledgerbook manuscript of a page of In Dubious Battle. The page is titled 'Dramatization,' and Steinbeck seems to be outlining what he wishes to accomplish in first chapters of book. RESTRICTED USE